Analysis of semiconductor InGaAsP/InP coupled microring resonators (CMRR) by time-domain travelling wave (TDTW) method - Amiri, I.S.; Ariannejad, M.M.; Ismail, Mohammad Faizal; Ahmad, Harith (Springer Verlag, 2017)
Analysis of a coupled microring resonators (CMRR) system made of InGaAsP/InP semiconductor is presented. This analysis exploited the time-domain travelling wave method in order to model the transfer function of the passive CMRR, and incorporated modeling of both passive and active MRRs filters wherein such filters are mostly characterized by their frequency response. Theoretical calculations of the system were performed using Vernier effects analysis, in which the Vernier operation with signal flow graph is a graphical approach for analyzing the intricate photonic circuits mathematically and allows for quick calculation of optical transfer function. Two MRRs, each having a radius of 32 µm, were vertically coupled together and used to generate resonant peaks. Narrow transmission peaks having bandwidths at full width at half maximum (FWHM) of 0.05 nm, corresponding to 6.24 GHz, were generated. The free spectrum range (FSR) of the pulses was 12 nm, which corresponded to 1.5 THz in the frequency domain. The finesse “F” given by FSR/FWHM was ~240, and the Q-factor obtained, which is the ratio of the resonant wavelength to the 3-dB bandwidth (FWHM), was ~3.1 × 104; such results are indicative of the system having a good performance. The dispersion and group delay of the CMRR has been presented as well.